Oncology nurse perceptions about life expectancy discussions: a cross-sectional study exploring what patients want to know, and why doctors don't disclose. Issue 5 (2nd November 2022) - Bryant, Jamie; Hobden, Breanne; Waller, Amy; Sanson-Fisher, Rob; Shepherd, Jan
Abstract : Background : Sensitive and patient-centred discussion about life expectancy has clear benefits for patients with advanced cancer and their families. The perceptions of oncology nurses about disclosure of life expectancy, and the barriers to disclosure, have rarely been explored. Objectives/Aims/Hypotheses : To examine oncology nurses' perceptions of the: (1) proportion of patients with advanced cancer who want, receive and understand estimates of life expectancy; (2) reasons why doctors may not provide estimates of life expectancy. Design : Cross-sectional survey. Methods : Australian oncology nurses who were members of a professional society or worked at a participating metropolitan cancer centre were emailed a link to an anonymous online survey. Participants provided socio-demographic characteristics and their perceptions about the proportion of patients with advanced cancer who (a) want, (b) are provided with, (c) receive and (d) understand estimates of life expectancy, as well as the reasons estimates of life expectancy may not be provided. Results : A total of 104 nurses participated. While 51% of nurses perceived that most patients (>75%) want to be provided with an estimate of their life expectancy, 63% of nurses reported that <50% of patients were provided with an estimate. Further, 85% of nurses indicated that <50% of patients understand the estimate. The most frequent reason nurses perceived doctors did not provide an estimate of life expectancy was because the doctor didn't have an accurate idea of life expectancy (80.8%). Almost one-fifth of nurses (18.3%) thought that doctors did not provide estimates because they felt it was not their responsibility to do so. Conclusions : Strategies to ensure a patient-centred approach to life expectancy discussions with patients with advanced cancer are urgently needed. Impact statement : Oncology nurses perceive that many patients with advanced cancer are not provided with an accurate estimate of their life expectancy and few understand the information provided to them.